Letter to Jane Tolmach from Assemblyman Julian C. Dixon - Julian C. Dixon:::::: (1976)
In a June 14, 1976 letter, Assemblyman Julian C. Dixon, Chairman of the Assembly Democratic Caucus, congratulated Jane Tolmach on her primary victory. He acknowledged that winning the Democratic nomination required strong organization and hard work and expressed pleasure that she would contribute to a strong Democratic showing in November. Dixon stated that he looked forward to working with and assisting her in the coming months.